Remodelling of extracellular matrix is a requirement for the hepatic progenitor cell response. Issue 4 (23rd November 2010) - Kallis, Yiannis N; Robson, Andrew J; Fallowfield, Jonathan A; Thomas, Howard C; Alison, Malcolm R; Wright, Nicholas A; Goldin, Robert D; Iredale, John P; Forbes, Stuart J
Abstract : Background and methods: In advanced liver damage, hepatic regeneration can occur through proliferation of a resident hepatic progenitor cell (HPC) population. HPCs are located within a designated niche in close association with myofibroblasts and bone marrow (BM) derived macrophages. Extra-cellular matrix (ECM) laminin invariably surrounds HPCs, but the functional requirement of this matrix-cell association is untested in vivo. Using the collagen Iα1 (r/r) mouse (r/r), which produces mutated collagen I resistant to matrix metalloproteinase degradation and has an exaggerated fibrotic response to liver injury, we test the relationship between collagen degradation, laminin deposition, and the HPC response. Results: Chronic fibrotic carbon tetrachloride (CCl4 ) injury can induce a florid HPC response associated with dense laminin deposition. In the recovery phase after chronic CCl4 injury, r/r mice have a markedly attenuated HPC response compared to wild-types, together with persistence of collagen I and failure to deposit ECM laminin. Similar results were found in r/r mice given the choline-deficient ethionine supplemented diet, another model of the HPC response. In cross-over sex-mismatched BM transplantation (BMT) experiments between r/r mice and wild-types, the blunted HPC response of r/r mice was not rescued by wild-type BMT and likewise not conferred on to wild-type recipients by r/r BMT, demonstrating that the attenuated HPC response in r/r mice is a property intrinsic to the liver. Conclusion: Failure of ECM remodelling after chronic fibrotic liver injury hinders the ability of the liver to activate HPCs. Laminin-progenitor cell interactions within the HPC niche are a critical for HPC mediated regeneration.